2011
DOI: 10.1007/s00592-011-0332-7
|View full text |Cite
|
Sign up to set email alerts
|

Three-year comparison of subcutaneous insulin pump treatment with multi-daily injections on HbA1c, its variability and hospital burden of children with type 1 diabetes

Abstract: Treatment with continuous subcutaneous insulin infusion (CSII) allows a large degree of treatment individualization and intensification in children with diabetes. The study’s aim was to evaluate the impact of treatment with CSII on glycated haemoglobin level (HbA1c) in children with diabetes and investigate whether introduction of CSII is associated with an increased risk of acute complications of diabetes. Patients treated throughout the recruitment period exclusively with multiple daily injections (MDI) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 28 publications
0
27
1
Order By: Relevance
“…A shorter T1D duration was significantly associated with a lower HbA1c level, even after adjusting for age and treatment . Several articles reported a strong association between the occurrence of DKA and/or microalbuminuria and HbA1c level, although no association between HbA1c level and hypoglycaemia was observed …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…A shorter T1D duration was significantly associated with a lower HbA1c level, even after adjusting for age and treatment . Several articles reported a strong association between the occurrence of DKA and/or microalbuminuria and HbA1c level, although no association between HbA1c level and hypoglycaemia was observed …”
Section: Resultsmentioning
confidence: 93%
“…In most studies, age was significantly and positively correlated with HbA1c level . Four small‐scale studies and one performed in a very early age at T1D onset reported non‐significant association.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The strength of this study is that although it is not a RCT, it analyses “real‐world” outcomes of a large population‐based cohort over a longer duration than previously reported. It differs from other pediatric studies which often include only a small number of patients, have a much shorter follow‐up time, and do not include a control group (patients on injection therapy) . Furthermore, data in this study come from a population‐based database with high case ascertainment, and pairs were matched with a random‐sampling algorithm that minimizes a potential selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the available data, we hypothesise that variability of HbA 1c may represent a 'breakthrough' effect of a sudden deterioration of metabolic control with the associated episode of microalbuminuria, both of which are subsequently resolved. If this is the case, protection from such events may be offered by interventions aimed at reducing the variability of HbA 1c , such as the introduction of insulin pump therapy [38]. The significance of HbA 1c variability as a risk factor of microalbuminuria development in patients with type 1 and type 2 diabetes has been confirmed recently [39,40].…”
Section: Discussionmentioning
confidence: 98%